Humane Entrepreneurial Framework: A model for effective corporate entrepreneurship. (4th May 2021) - Kim, Ki-Chan; Hornsby, Jeffrey S.; Enriquez, John Laurence; Bae, Zong-Tae; El Tarabishy, Ayman
ABSTRACT: The concept of Entrepreneurial Orientation (EO) has been an important construct of entrepreneurship and business strategy since it was first introduced in 1983 by Danny Miller. Still, it does not fully address the human-centered factors influencing organizations today. Therefore, the concept of humane entrepreneurship (HumEnt) was introduced to better understand organizations' human side of entrepreneurial development. HumEnt explores how effective people management practices affect employee engagement, innovation, and business growth. The new concept of Humane Entrepreneurial Framework outlines the process of creating HumEnt that focuses on the people side of the business, introducing the elements of high-performance work systems (HPWS) to a company's entrepreneurial strategy. Building on HPWS and EO research, this article proposes a model suggesting that a "humane" approach to managing employees is a key antecedent to creating and maintaining EO; furthermore, humane organizational practices ultimately lead to sustainable entrepreneurship and innovation in companies. Future research directions are also offered.